A gait generating algorithm with smooth speed transition for the locomotion of legged robots. (April 2014) - Wang, Jianhua; Wen, Jintao; Chen, Weihai; Yue, Haosong; Liu, Dong
Much of what is known about the gait-generated method is based on specified gait pattern. Yet in the wild, animals can move over terrains with widely varying properties in various gait patterns. Previous studies have realized gait types such as trot or walk in various legged robots, but no detailed relationship descriptions of different gaits are currently available. This paper addresses the intrinsic relationship between all kinds of gait for legged robot locomotion in order to realize the gait transition smoothly. Based on their relations, the proposed gait-generated method is constructed by a support factor and a delay factor, which describe locomotion efficiency and leg difference motion, respectively. A gait ring concept is proposed to explain their intrinsic relation, and a gait algorithm is proposed to realize the speed transition for legged robot locomotion. A quadruped robot called MATA_ I with 12 DOFs is specially designed for realizing gait transition. This kind of robot has a 4RRRS parallel motion structure, and each joint is driven by motor modules. The algorithm with smooth transition between different gaits was applied in this kind of robot. The simulation results have shown that the proposed gait-generated algorithms can effectively realize gait transition for legged robot.